232k views
4 votes
Please help.
Simplify the expression using imaginary numbers.
2 √ -16 + √ -9

User DrWaky
by
5.0k points

2 Answers

4 votes

Answer:

11i

Explanation:

These roots are imaginary, but let's make it so that i=the square root of -1. simplify the two roots to get 4i and 2i. Multiply the 4i by 2 to get 8i. add them together to get 11i

TL;DR

2x4i+3i

8i+3i

11i

User Isaac Wasserman
by
4.8k points
1 vote

Since, by definition,
i^2=-1, we deduce that
√(-1)=i

So, we have


2√(-16)+√(-9)=2√(-1\cdot 16)+√(-1\cdot 9)=2+√(-1)√(16)+√(-1)√(9)=2\cdot i\cdot 4+3i=8i+3i=11i

User Grismar
by
4.8k points